PERANCANGAN GALERI SENI INTERAKTIF DIGITAL DI SURABAYA DENGAN PENDEKATAN ARSITEKTUR MODERN - Azi Setia Pramuja; Tigor WSP; Farida Murti (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2024)
In this millennial era, many children want to experience an identity crisis due to social media that makes them In this millennial era, many children want to experience an identity crisis due to social media that makes them tech savvy, from this, many make the creative economy sector also offset what is in demand from young people today, one of which is the art gallery that raises art with interactive concepts with digital media that are many interesting visitor interest. From the conditions above, the creative economy sector is starting to develop its wings and innovate to follow trends for the needs of this social media event, such as making many contemporary products that are in demand and places to visit instagrammable , one of which is in the arts sector.